REVIEWS ON UNITS OF APPEAL FOR CHILDREN (Scientific journal of the Fergana State University, 2023)
The application forms in the article must comply with the laws of communication in any communication. If the application forms are not chosen correctly, then the communication will not be effective. According to Formanovskaya, appeals are part of a wide range of speech etiquette, as these units are used to establish and maintain communication with the interlocutor, in general, to provide detailed views on the regulation of social and personal relations between the speaker and the listener. The article also compares the units of appeal for children in Russian and Uzbek families.